Analysis of Morphometric Character of Chromis Fish in Indonesia and Korea - Lee, Jae Won; Mustaruddin, Mustaruddin; Murdiyanto, Bambang; Wahju, Ronny Irawan; Koo, Kim Jin (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2018)
There are more than 350 species of Chromis fish in the world. Its distribution covers tropical and subtropical water areas. Spesific geographical conditions determine fish development.Â This study aims to analyze morphometric meristik, and the differences between chromis fish characters in Indonesia and Korea waters. The research methods were consisted of descriptive methods, Kruskal-Wallis, and Mann Whitney test.The result showed the total length of Abudefduf sexfasciatus found in Palabuhan ratu and Pramuka Island water territories are ranged from 9.9 to 10.2 cm and 7.7 to 13.0 cm.This fish has a dorsal fin, caudal fin which consists of 12-17 weak fingers, and ventral fin consists of 1 hard finger and 4-6 weak fingers. Abudefduf vaigiensisâ€™ found in Palabuhan ratu, Buton Island, Sorong, and Korea water has each ranging total length from 6.0 to 10.6 cm, 10.9 -12.3 cm, 11 cm, and 5.0 to 8.6 cm.The differences are in the caudal and ventral fin. Morphometric characters of Abudefduf sexfasciatus found in Palabuhan ratu and Pramuka Island water territories relatively similar. Morphometric characters of Abudefduf vaigiensis found in Korean waters was not significantly different with Palabuhan ratu, Buton Island, and Sorong water territories. Compared with the other two locations, Abudefduf vaigiensis found the island of Buton water territory has closely related family with the Korean waterâ€™s